EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN LITERASI MATEMATIS PESERTA DIDIK MTS - Sri Wulandari; Nursupiamin Nursupiamin; Rafiq Badjeber (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research aims to determine the effectiveness of the Problem Based Learning (PBL) learning model on the mathematical literacy abilities of MTs students. This type of research using a quasi-experimental approach. The research design is in the form of (pre-test-post-test with control group). The research resulst showed that there was an increase in students’ mathematical literacy skills by looking at the t-test data. The average post-test value for the experimental class was 78,4912 while the control class obtained an average value of 76,2059. So it can be concluded that the Problem Based Learning (PBL) leraning model is effective on the mathematical literacy abilities of MTs students